Advertising to children on TV : content, impact, and regulation - Gunter, Barrie (Lawrence Erlbaum, 2005)
The growth of TV platforms in terrestrial, satellite, and cable formats will soon move into digital transmission. These all offer opportunities for greater commercialisation through advertising on media that have not previously been exploited. This book looks to the future in considering how effective codes of practice and regulation will develop.